PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS MATERI LUAS BANGUN DATAR PESERTA DIDIK KELAS IV SDN ROGOMULYO 02 KECAMATAN KAYEN KABUPATEN PATI - Fajar Adi Lumaksono; Sukamto; Khusnul Fajriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of the Quantum Teaching model as well as measure its impact on improving mathematical reasoning of fourth grade students of SDN Rogomulyo 02 Kayen Subdistrict, Pati Regency for flat area material. The pre-experimental one-group pretest-posttest design was applied to 30 students. The instruments applied included mathematical reasoning tests, learning motivation questionnaires, and observation sheets. The findings indicated an increase in the mean score from 60.58 in the pretest to 81 in the posttest. The t-test confirmed the significance with a p value = 0.001, which is smaller than 0.05, as well as an N-Gain score of 0.53, which is in the moderate category. About 83.33% of students showed high to very high levels of learning motivation. Observations also noted a consistent improvement in the application of the TANDUR model and student engagement. Overall, the Quantum Teaching model proved effective in improving mathematical reasoning skills through interactive and meaningful learning experiences.